KIP-K Scholarships and Student Engagement: The Role of Organizational Commitment in Academic and Social Activities - Jannah, Miftahul; Melandari, Defi; Arifin, Syamsul (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study examines the effect of the KIP Kuliah Scholarship on student engagement, both directly and indirectly through organizational commitment, within the context of a private higher education institution in Indonesia. Using a quantitative approach and structural equation modeling with SmartPLS 4, data were collected from KIP Kuliah scholarship recipients to analyze the proposed relationships. The results indicate that the KIP Kuliah Scholarship has a positive and significant effect on organizational commitment and student engagement. The structural model shows strong explanatory power, with an R² value of 0.600 for organizational commitment and 0.876 for student engagement, suggesting that student engagement is largely explained by the combined influence of financial support and organizational commitment. Mediation analysis confirms that organizational commitment plays a significant mediating role in strengthening the relationship between the KIP Kuliah Scholarship and student engagement. This study contributes theoretically by demonstrating organizational commitment as a key internalization mechanism through which external financial support is transformed into sustained student engagement, thereby extending existing scholarship literature beyond direct-effect models.